The use of statistics in microarray studies - Wit, Ernst (Henry Stewart Talks, 2009)
Statistics is a vital tool in microarray studies, From formulating the research questions, via cleaning up the data, to inferring the results, statistics is involved in all aspects of a microarray experiment, Where the need for statistics comes from, The omnipresence of artifacts in the data, The considerable variability between replicates and the general (random) variation of the data
Archived at 2021/02/25